Association between vitamin D deficiency and otitis media with effusion in children: a systematic review and meta-analysis - Restuti, Ratna Dwi; Safitri, Eka Dian; Ranakusuma, Respati Wulansari; Sriyana, Ayu Astria; Priyono, Harim; Saleh, Rangga Rayendra; Marpaung, Dora A; Lazarus, Gilbert (Paediatrica Indonesiana, 2024)
Background Vitamin D plays a crucial role in the regulation of inflammation. However, its effect on the development of otitis media effusion (OME), an inflammatory disease of the middle ear without signs of infection, remains largely unknown. Objective To assess the association between vitamin D deficiency and OME in children by systematic review and meta-analysis of the literature. Methods Eligible studies retrieved from PubMed, ProQuest, Embase, Cochrane databases and trial registries published up to 30 October 2022 were included in this review. The risk of bias of the included articles was assessed with the JBI Critical Appraisal Checklist for observational studies. The certainty of evidence was assessed with the Grading of Recommendations Assessment, Development and Evaluation framework. Results We included eight studies (six case-control and two cross-sectional studies) involving 1,114 children, of which four studies were eligible for meta-analysis due to the significant clinical heterogeneity. We found that vitamin D deficiency (defined as vitamin D concentration of 20 ng/mL or less, i.e., ?50 nmol/L) might increase the odds of developing OME by 66.0% (n=514; OR 1.66; 95%CI 1.09 to 2.54; I2=20%), albeit with a very low certainty of evidence. Conclusion There is a very low quality of evidence indicating that vitamin D deficiency is associated with the development of OME in children. Further large, high-quality cohorts and adjusting for confounding factors are warranted to confirm our findings, ideally by exploring the dose-response relationship between vitamin D concentration and the development of OME.